iSmashON: a mobile application for social networking and badminton court booking / Muhamad Akmal Adha Radzuan ... [et al.] - Radzuan, Muhamad Akmal Adha; Jamaluddin, Muhammad Nabil Fikri; Abd Halim, Iman Hazwam; Mohd Fuzi, Mohd Faris; Ibrahim, Alif Faisal; Hamid, Ros Syamsul (UiTM Cawangan Perlis, 2024)
Badminton is a thrilling and competitive sport that has gained popularity across the world, attracting players of all ages. The sport fosters social interaction among players which helps create friendships and engagement within a community. Although many local sport centres provide badminton courts, some facilities lack a systematic way to handle bookings. The booking process can be frustrating and time-consuming. This may result in delayed replies, miscommunication and conflicting booking information. In this paper, we present iSmashON, a mobile application developed to simplify the booking process by providing systematic way of booking badminton courts, chat with other players and manage bookings. It features real-time availability updates and personalized notifications. The development encompasses four phases which are requirement analysis, design and development, testing and refinement. The evaluation of the developed mobile application is done using Technology Acceptance Model (TAM) that considers four componentswhich are Perceived Ease of Use (PEU), Perceived Usefulness (PU), Attitude (ATT) and Behavioural Intention (BI). Questionnaire with 13 questions is prepared and distributed over 30 respondents with at least one-year experience of playing badminton. Results from the TAM evaluation shows a favourable attitude among respondents towards using the mobile application as a medium for booking badminton courts. This is drawn by the highest mean score obtained from ATT component. It is believed that the iSmashON application is expected to enhance the booking experience, providing more efficient and user-friendly process that will be benefited by badminton community.